Pengembangan Literasi Desa Melalui Pemberdayaan Masyarakat Di Bidang Ekonomi (UMKM-Pariwisata) Dan Transformasi Digital - Rizqon Hoeroni; Sindik Widati; Sinta Sundari Heriyanti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of community engagement carried out by university students through an interdisciplinary, institutional, and partnership-based approach as a realization of the Tri Dharma of Higher Education. This program is mandatory and is based on the principles of academic competence, entrepreneurship, and professionalism in order to produce high-quality, relevant, and synergistic community service activities that enhance community empowerment. Based on this background, the KKN program was implemented in Sukadami Village with the objective of providing basic knowledge and skills, particularly in the fields of education, religion, and governance. The main issues identified in the village were related to the quality of human resources, especially the low level of digital literacy in supporting UMKM activities and tourism development. Therefore, the KKN activities aimed to address these challenges and foster a digitally literate community. The results of the program indicate an increase in sales turnover of local UMKM products and improved community satisfaction following the renovation of the local fishing facility.